Development of renewable energy system integrated with hydrogen and natural gas subsystems for cleaner combustion - Ozturk, Merve; Dincer, Ibrahim (ELSEVIER SCI LTD, 2020)
This paper proposes a novel integrated system for hydrogen and natural gas blending system for a selected residential application. In the current system, hydrogen is generated via an alkaline water electrolyzer unit, and the electricity required for the electrolyzer is supplied from renewable sources, i.e., solar PV panels and wind turbines. The remaining electricity is supplied to the building where the system will be built. The whole system is evaluated using the Aspen Plus software and Engineering Equation Solver (EES). The hydrogen fraction is increased by volume from 0% to 20% in the blend while the natural gas volume fraction is decreased from 100% to 80%. With the increase of hydrogen injection, carbon dioxide emissions from the combustion unit are reduced. According to the performance assessment, the highest values for the overall energy and exergy efficiencies are 67.3% and 53.2%, respectively in March and their lowest values are 58.4% and 44.2%, respectively in December.
Keywords: Natural gas; Hydrogen; Alkaline electrolyzer; Efficiency; Solar energy; Wind energy; EMISSIONS; Energy & Fuels; Engineering